HUBUNGAN EFIKASI DIRI DENGAN PERILAKU PROSOSIAL PADA GURU PAUD KABUPATEN INDRAGIRI HILIR - Hanisah Hanisah; Yeni Solfiah; Rita Kurnia (UIR PRESS, 2019)
This study aims to determine the correlation between self-efficacy and prosocial behavior for early childhood and teachers in the Tagbilaran Hulu sub-district Indragiri Hilir. The population of this study is about 42 early childhood and teachers in the Tembilahan Hulu sub-district Indragiri Hilir. This study used a quantitative correlation to determine the correlation between the independent and dependent variables. The data collecting technique used questioners on a Likert scale. the result of the test was analyzed by using Likert scale trial through IBM SPSS (statistical package for social science) version 23. from the analysis, it was showed that there is a positive correlation between self-efficacy and prosocial behavior for early childhood and teachers in the Tembilahan Hulu sub-district Indragiri Hilir. It can be seen from the correlation coefficient rxy = 0,396 with significance 0.010<0.05. The category is low with determinant coefficient KD = r2 x 100% = 0,396 x 100% = 15,69% it is mean that self-efficacy influences about 15,69% to the prosocial behavior.